Indonesian Students Awareness of Verbal and Non-Verbal Intercultural Differences at the Global Workplace - Isry Laila Syathroh; Intan Satriani Satriani; Iman Santoso (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2019)
The aim of this paper is to describe Indonesian students awareness about cultural differences happens in the global workplace. The students followed 600 minutes of Intercultural Communication course in six weeks. The research involved 36 students of English Education Department, who filled out 12 questions of questionnaire about cultural awareness. The result showed that most students had proper verbal and nonverbal awareness related with the intercultural differences at the global space. The result was supported by Hanvey (1979) statement who stated that the level of most students at level three. They were aware of significant and subtle cultural traits that contrast markedly with ones own but can be understood cognitively. This research suggests that the next researcher can dig more perspective not only from students but also from other occupations. Besides that, another instrument like interview or participant observation also can be applied to get more information.